2003
DOI: 10.1074/jbc.m212950200
|View full text |Cite
|
Sign up to set email alerts
|

An Extended LXXLL Motif Sequence Determines the Nuclear Receptor Binding Specificity of TRAP220

Abstract: The interaction of coactivators with the ligand-binding domain of nuclear receptors (NRs) is mediated by amphipathic ␣-helices containing the signature motif LXXLL. TRAP220 contains two LXXLL motifs (LXM1 and LXM2) that are required for its interaction with NRs. Here we show that the nuclear receptor interaction domain (NID) of TRAP220 interacts weakly with Class I NRs. In contrast, SRC1 NID binds strongly to both Class I and Class II NRs. Interaction assays using nine amino acid LXXLL core motifs derived from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 58 publications
3
33
0
1
Order By: Relevance
“…Biochemical and genetic evidence strongly suggest a mechanism in which different (promoter-bound) activators recruit Mediator through interactions with distinct Mediator subunits (4,21,26). Relevant to the present study, many nuclear receptors have been shown to interact, in a ligand-dependent manner, with the Mediator MED1/TRAP220 subunit, through interactions between the liganded AF2 receptor domain and the MED1/TRAP220 LXXLL motifs (8,20,30,32,33,38,39,43,44), and studies of mutated Mediator complexes have established a key role for MED1/TRAP220 and resident LXXLL domains in strong interactions between TR␣ and the complete Mediator complex (25).…”
Section: Discussionmentioning
confidence: 80%
“…Biochemical and genetic evidence strongly suggest a mechanism in which different (promoter-bound) activators recruit Mediator through interactions with distinct Mediator subunits (4,21,26). Relevant to the present study, many nuclear receptors have been shown to interact, in a ligand-dependent manner, with the Mediator MED1/TRAP220 subunit, through interactions between the liganded AF2 receptor domain and the MED1/TRAP220 LXXLL motifs (8,20,30,32,33,38,39,43,44), and studies of mutated Mediator complexes have established a key role for MED1/TRAP220 and resident LXXLL domains in strong interactions between TR␣ and the complete Mediator complex (25).…”
Section: Discussionmentioning
confidence: 80%
“…1B). Previous screens with coactivator peptides established amino acid residues at ϩ6 to ϩ12 as critical for binding (38,42). To capture these specificity determinants, peptides of 20-amino acid length were generated.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Y537 (the human equivalent of mouse Y541) does not appear to be in close contact with the LXXLL core motif sequence. However, sequences flanking the core motifs are known to be important for differential interactions of coactivators with steroid receptors and other NRs (Needham et al 2000, Coulthard et al 2003, although such sequences have yet to be observed in LBD/coactivator peptide crystal structures. Thus, it remains to be established how replacement of Y541 with alanine or acidic residues enhances ligand-independent binding of coactivators in mammalian cells.…”
Section: Discussionmentioning
confidence: 99%